Glassy dynamics due to a trajectory phase transition in dissipative Rydberg gases - Pérez-Espigares, Carlos; Lesanovsky, Igor; Garrahan, Juan P.; Gutiérrez, Ricardo (American Physical Society, 2018)
The physics of highly excited Rydberg atoms is governed by blockade or exclusion interactions that hinder the excitation of atoms in the proximity of a previously excited one. This leads to cooperative effects and a relaxation dynamics displaying space-time heterogeneity similar to what is observed in the relaxation of glass-forming systems. Here, we establish theoretically the existence of a glassy dynamical regime in an open Rydberg gas, associated with phase coexistence at a first-order transition in dynamical large deviation functions. This transition occurs between an active phase of low density in which dynamical processes take place on short timescales, and an inactive phase in which excited atoms are dense and the dynamics is highly arrested. We perform a numerically exact study and develop a mean-field approach that allows us to understand the mechanics of this phase transition. We show that radiative decay—which becomes experimentally relevant for long times—moves the system away from dynamical phase coexistence. Nevertheless, the dynamical phase transition persists and causes strong fluctuations in the observed dynamics.